(untitled) (International Journal of Economics Management and Social Science, 2026)
This study aims to examine the income levels and poverty status of coffee farmers in Bengkulu Province, Indonesia, by comparing outcomes between those adopting grafting techniques and those using conventional cultivation methods. The study applies the poverty classification framework, using rice equivalent income thresholds, and incorporates rural poverty literature related to agricultural productivity and institutional access. Primary data were collected through structured interviews with 326 purposively selected coffee farmers. Income analysis was employed to determine income level, and poverty analysis was used to examine the level poverty among farmers. The findings reveal that farmers who adopted grafting techniques achieved a higher average income (USD 1,340.8) compared to those using conventional methods (USD 1,154.7). The adoption of grafting reduced the poverty rate by 22.71%, assuming land ownership. The study suggests that promoting technological adoption and strengthening farmer institutions are crucial for reducing rural poverty. This study provides empirical evidence on the economic impact of grafting in smallholder coffee farming and offers actionable insights for rural development policies. It contributes to the broader discourse on sustainable agriculture and poverty alleviation in developing economies